Peran Koneksi Politik Dalam Memoderasi Pengaruh Karakteristik Dewan Direksi Terhadap Manajemen Laba Riil - Manopo, Sharon; Nugrahant, Yeterina Widi (E-Jurnal Akuntansi; Vol 33 No 8 (2023), 2023)
This study aims to examine the characteristics of the board of directors on real earnings management with political connections as a moderator. The characteristics of the board of directors used in this research include managerial share ownership, educational background, tenure and gender of the board of directors. The research sample used is a manufacturing company listed on the IDX. SAMPLING using purposive sampling and obtained as many as 348 observations. Panel data is processed with the GLS model. The results of the study found that board of directors share ownership has a negative effect on real earnings management. The educational background of the board of directors in accounting, business or finance was found to have a negative effect on real earnings management. A board of directors with a long term of office was found to have no influence on real earnings management, while research results between the gender of the female board of directors were found to have a significant influence on real earnings management. Political connection was found to have no effect on board of directors share ownership, tenure on real earnings management. Political connections were found to have a negative influence between the educational background of the board of directors on real earnings management. The presence of political connections will strengthen the negative influence of the educational background of the board of directors on earnings management. Political connections were found to have a significant positive effect or to moderate the relationship between female board of directors gender and real profit management. Keywords: Real Earnings Management; Political Connection; Board of Directors Characteristic; Female Board of Directors